Alterações na antropometria e na qualidade de vida relacionada à saúde após um programa de exercícios aquáticos em crianças com sobrepeso e obesidade - Reis, Marina de Melo (2020)
The aim this study was to evaluate the changes in anthropometric parameters and health-related quality of life (HRQoL), post aquatic program intervention among overweight and obese children. This non-randomized controlled clinical trial was performed in Uberaba, Minas Gerais with 33 children, mean age of 9,10 ± 1,00 years, of both sex. Children were allocated in control group (CG; n = 21) and experimental group (EG; n = 12). The EG performed 21 weeks of the aerobic recreative aquatic exercise, 54 sessions each 60 minutes. At baseline and post intervention, body mass, height, BMI and the HRQoL by Pediatric Quality of life Inventory (Pedsql version 4.0) were assessed. A significant time effect in the emotional aspect to HRQL reported by children (p = 0,009) was observed, that is, there was a score reduction in EG and a score increase in CG. There was tendency to time*group interaction effect (p = 0,059) for the school activities dimension, with a score reduction in EG and score increase in CG after 21 weeks. No significant change was observed in the anthropometry or HRQL reported by parents in both groups. In conclusion, there was significant change in emotional dimension reported by children, however, the intervention did not significantly change the anthropometry and other HRQoL dimensions in overweight or obesity of children.